2006
DOI: 10.1111/j.0012-155x.2006.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Cleaner Production Programmes in Changzhou and Nantong, Jiangsu Province

Abstract: Cleaner Production (CP) has been advocated worldwide as a strategy for companies to obtain environmental and economic benefits simultaneously. This analysis of how city-level CP programmes were implemented in Changzhou and Nantong (Jiangsu Province, China) finds that both cities failed to meet the Province's targets to implement CP at all large-and medium-sized companies by the end of 2000. Ineffective vertical control, weak inter-agency co-ordination, and lack of alignment between CP requirements and the core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…Although some progress have been made, the case also shows that there are some common existing barriers as other regions in China, such as a lack of the establishment of an adequate institutional framework, a basic lack of awareness capacity and resources among enterprises, and the difficulty in creating a market for CP services (He and Ortolano, 2006;Fang and Cote, 2005;Shi et al, 2008;Hicks and Dietmar 2007;Heidi et al, 2005;Oliver and Ortolano, 2006). Unlike other case studies in Zhejiang (Hicks and Dietmar 2007), Nantong and Changzhou (He and Ortolano, 2006), and Taiyuan (Heidi et al, 2005), the provincial government has a more comprehensive consideration for promoting CP implementation in Liaoning.…”
Section: Discussion On Suggestions For Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some progress have been made, the case also shows that there are some common existing barriers as other regions in China, such as a lack of the establishment of an adequate institutional framework, a basic lack of awareness capacity and resources among enterprises, and the difficulty in creating a market for CP services (He and Ortolano, 2006;Fang and Cote, 2005;Shi et al, 2008;Hicks and Dietmar 2007;Heidi et al, 2005;Oliver and Ortolano, 2006). Unlike other case studies in Zhejiang (Hicks and Dietmar 2007), Nantong and Changzhou (He and Ortolano, 2006), and Taiyuan (Heidi et al, 2005), the provincial government has a more comprehensive consideration for promoting CP implementation in Liaoning.…”
Section: Discussion On Suggestions For Improvementsmentioning
confidence: 99%
“…Heidi et al (2005) assessed energy related cleaner production projects in Taiyuan city from the point of view of climate change and integrated assessment. In addition, Oliver and Ortolano (2006) studied how city-level cleaner production programmes can function for the implementation of cleaner production by employing a case study approach in both Changzhou city and Nantong city. Their findings show us that ineffective vertical control, weak inter-agency coordination, and lack of alignment between CP requirements and the core missions and operating procedures of implementing agencies have impeded CP implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of barriers exist in the introduction, development and application of CP in Chinese enterprises. Oliver and Ortolano (2006) studied cleaner production implementation in both Changzhou city and Nantong city and found that ineffective vertical control, weak inter-agency coordination, and lack of alignment between CP requirements and the core missions and operating procedures of implementing agencies had impeded CP implementation in China. Shi et al (2008) also found that lack of economic incentive policies, lax environmental enforcement, and high initial capital cost are the top three barriers to CP adoption/development by Chinese Small and Medium Enterprises (SMEs).…”
Section: Introductionmentioning
confidence: 99%
“…We propose a priori that local government's incentive is one of the most influential factors to the formations of local CP strategies; and varied strategies bring out different CP policy impacts and outcomes in various places. Adapted from conceptual framework by Oliver and Ortolano (2006) [17], which was designed for analyzing the implementation of the CP program, we focus the analytical framework on internal incentives and the corresponding implementation strategy of local government. Figure 2 shows our framework for an analysis of CP policy implementation at city level in Hangzhou and Guiyang.…”
Section: Framework For Analyzing Local Cp Policy Implementationmentioning
confidence: 99%
“…Many barriers exist in China's CP promotion procedure, such as the lack of co-benefit calculation demonstration [14], low awareness and misconception of CP, inadequate institutional framework, constraints in technological facilities and financial support, limited market of CP services, internal conflicts of implementing agencies, and so on [13,[15][16][17]. In order to overcome these barriers, regional government could improve coordination between stakeholders, provide subsidies and increase capacity-building programs [17]. In addition, government could also ensure the continuity and rigorousness of CP projects [13] and encourage enterprises by calculating their project's profit-generating potential [13,18].…”
Section: Introductionmentioning
confidence: 99%